2009
DOI: 10.1111/j.1472-8206.2009.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and antiproliferative effects of astaxanthin during the initiation stages of 1,2‐dimethyl hydrazine‐induced experimental colon carcinogenesis

Abstract: Colon cancer is one of the major causes of cancer mortality worldwide. Several carotenoids with antioxidant properties are reported for their chemopreventive nature. In this study, we have evaluated the chemopreventive efficacy of astaxanthin on lipid peroxidation, antioxidant status, total number of aberrant crypt foci (ACF), and cell proliferation in 1,2 dimethylhydrazine (DMH)-induced colon carcinogenesis using a rat model. DMH was induced subcutaneously at a dosage of 40 mg/kg body weight, twice a week for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…Canthaxanthin and astaxanthin have been detected physiologically in human breast tissue, and the amount is inversely related to the frequency of malignant lesions (11). In agreement with our present protocol, the inhibitory effects on mouse fibrosarcoma cells were evident only when astaxanthin intake was started 1 or 3 weeks before transplantation (12), and oral astaxanthin intake at the preinitiation stage reduced the incidence of 1,2-dimethylhydrazineinduced rat colon aberrant crypt foci and crypt cell proliferation more significantly than intake during the post-initiation stage (13). Accordingly, the present study demonstrated that a potent anticancer effect was observed in rats fed a diet containing 0.4% astaxanthin.…”
Section: Discussionsupporting
confidence: 78%
“…Canthaxanthin and astaxanthin have been detected physiologically in human breast tissue, and the amount is inversely related to the frequency of malignant lesions (11). In agreement with our present protocol, the inhibitory effects on mouse fibrosarcoma cells were evident only when astaxanthin intake was started 1 or 3 weeks before transplantation (12), and oral astaxanthin intake at the preinitiation stage reduced the incidence of 1,2-dimethylhydrazineinduced rat colon aberrant crypt foci and crypt cell proliferation more significantly than intake during the post-initiation stage (13). Accordingly, the present study demonstrated that a potent anticancer effect was observed in rats fed a diet containing 0.4% astaxanthin.…”
Section: Discussionsupporting
confidence: 78%
“…1, 2 Dimethyl hydrazine and azoxymethane (AOM) are frequently used to induce colon cancer in rodents (Prabhu et al, 2009;Norazalina et al, 2010;Nurul-Husna et al, 2010;Ashokkumar and Sudhandiran, 2011). The spectrum of AOM-induced epithelial lesions resembles those of the various types of neoplastic lesions in human CRC.…”
Section: Animal Models For Colon Cancermentioning
confidence: 99%
“…Chemoprevention refers to the use of natural or synthetic compounds to prevent, reverse, or delay the development of cancer (Swan & Ford, 1997). Because food derived products exist universally and are expected to be safe, they are highly interesting for development as chemopreventive agents to treat cancer (Sengupta et al, 2002;Prabhu et al, 2009;various fruits and vegetables and has contributed to the antioxidant activity of artichoke leaf extract on reactive oxygen species in human leucocytes (Perez-Garcia et al, 2000). Luteolin is also reported to have anti-inflammatory properties and mediates its action by inhibiting of nitric oxide production (Kim et al, 1999).…”
Section: Introductionmentioning
confidence: 99%